1994
DOI: 10.3354/dao020095
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells in the swimbladder of Atlantic salmon Salmo salar:histochemistry and responses to compound 48/80 and formalin-inactivated Aeromonas salmonicida

Abstract: Observations were made on t~s s u e spreads from the swimbladder of the Atlantlc salmon Salmo salar The t~ssues were f~x e d In ethyl alcohol and stalned with alcoholic thionin All preparations showed numerous tlssue mast cells The dlstr~bution of the mast cells resembled thelr distribution In mammalian tissues, with a concentration In the vlclnity of the vascular network Mast cell degranulatlon could be demonstrated at 2 h after lntrapentoneal ~nlectlons of compound 48/80, but In fish kllled at 24 and 48 h, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 13 publications
5
24
1
Order By: Relevance
“…The latter authors described degranulation of eosinophilic granular cells in swim bladders and peritoneum following injection with bacteria. These cells have been known to occur in salmonid tissue, where they respond to various bacterial products (Ellis 1985, Vallejo & Ellis 1989, Powell et al 1993, Reite & Evensen 1994. In addition, the present work shows that thionin-postive cells occur in brown trout fin epidermis, where they seem to degranulate upon infection with skin parasites.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The latter authors described degranulation of eosinophilic granular cells in swim bladders and peritoneum following injection with bacteria. These cells have been known to occur in salmonid tissue, where they respond to various bacterial products (Ellis 1985, Vallejo & Ellis 1989, Powell et al 1993, Reite & Evensen 1994. In addition, the present work shows that thionin-postive cells occur in brown trout fin epidermis, where they seem to degranulate upon infection with skin parasites.…”
Section: Discussionsupporting
confidence: 47%
“…The exact nature of these cells is not clear but due to the metachromatic staining with thionin following fixation in absolute ethanol they fit the description of teleost mast cells provided by Reite (1998). Morphologically they corresponded to the swim bladder mast cells described by Reite & Evensen (1994) and to similarly stained cells seen by control staining of rainbow trout swim bladder performed by the present authors (data not shown). The function of these putative mast cells in the trout fin are unknown.…”
Section: Discussionmentioning
confidence: 57%
“…Later, the inflammatory response was evaluated by ink injection (Ellis et al, 1976), complete Freund's adjuvant and Staphylococcus aureus (Finn and Nielsen, 1971), carrageenin (Timur et al, 1977), Escherichia coli lipopolysaccharide (LPS), complete Freund's adjuvant, turpentine and carrageenin (White et al, 1981), Vibrio alginolyticus (MacArthur et al, 1984), liquid paraffin (Suzuki, 1986), Edwardsiella ictaluri LPS (Saeed and Plumb, 1986), Pseudomonas alcaligenes and Aeromonas punctata (Siwicki and Studnicka, 1987), Aeromonas salmonicida (Reite and Evensen, 1994), LPS (Brunetti et al, 1994), Freund's adjuvant and squalene (Jenkins and Klesius, 1998), microcystin (Vajcová et al, 1998), Escherichia coli , peptidoglican (Kono and Sakai, 2001), beta-glucan of Saccharomyces cerevisiae and Salmonella typhimurium LPS (Paulsen et al, 2001) and Mycobacterium marinum (Gauthier et al, 2003). In these studies, the inflammation was characterized by showing macrophages, leucocytes, fibroblasts and fibroplasia.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in the present study suggest that neutrophil migration stimulating factor(s) are released by degranulation of EGCs in tilapia. (Ellis, 1985;Vallejo and Ellis, 1989;Powell et al, 1991Powell et al, , 1993Reite and Evensen, 1994;Reite 1997Reite , 1998, and the accumulation of leucocytes after degranulation of the EGCs have been reported (Reite, 1997;Reite and Evensen, 1994;Matsuyama and lida, 1999 a).…”
Section: Cells and Its Effect On Neutrophil Migrationmentioning
confidence: 99%